Analysis of the Effect of Sitting Online Learning Position with Back Pain on Medical Students - Ayu Andira Sukma (Faculty of Medicine Universitas Mataram, 2022)
Back pain has become a phenomenal in itself in society because the higher and the earlier the incidence, which causes a decrease in the productivity of the individual. This case is also increasing during the Covid 19 pandemic, where learning activities, discussions, meetings or other activities are carried out online which require a person to sit in front of a computer or mobile phone for a long period of time without regard to position during online activities. In medical students this is also very influential, they are at high risk of spinal pain because they have a very dense curriculum that makes their lifestyle become sedentary, stressful daily activities, less hours of sleep, long study hours, practicum, and successive class schedules. The purpose of this journal literature is to analyze the effect of online learning positions on medical students with the incidence of spinal pain. Journal searches are carried out through Google Scholar by filtering research journals indexed nationally and internationally from 2016-2021. The results showed that there was an effect of online learning position on the incidence of spinal pain in medical students.